Preparação e caracterização de supercapacitores utilizando carbonos nanoestruturados, eletrólitos aquosos, orgânico e líquidos iônicos - Mayara Cele Gonçalves Santos (2020)
In the present work, electric double layer capacitors were developed employing different carbon materials (activated carbon, carbon nanotubes and mesoporous carbon) as electrodes, and aqueous, organic and ionic liquids - ILs (with different types of cations and anions) electrolytes. The work aimed to analyze the influence of the different carbon materials and ionic liquids on the stability and efficiency of supercapacitors prepared with these materials, as well as their comparison with cells prepared with aqueous and organic electrolytes, with a focus on the establishment of the working potential of the devices. Thus, a method to determine the electrochemical stability window and cell parameters for devices based on ionic liquids was established based on the study of coulombic efficiency and energy efficiency. In addition, symmetrical devices and an asymmetric cell constructed with nanocomposite materials (mesoporous carbon combined with different carbon nanotubes and reduced graphene oxide) electrodes and ionic liquids [EMI] [BF4] were studied, aiming the improvements in capacitance, energy densities and power density. The evaluation of devices constructed from nanocomposites showed that the addition of 30% of nanofillers to the mesoporous matrix was effective in obtaining composite materials with higher values of electrical conductivity, which resulted in supercapacitors with superior properties in relation to those prepared with the starting materials and other composites cited in the literature. Finally, the electrochemical properties of a buckypaper nanocomposite electrode formed by carbon nanotubes with double and triple walls and cellulose nanofibrils were evaluated with the use of different redox electrolytes. The composite buckypaper had excellent physical-chemical properties, including low electrical resistivity (20.3 S cm-1) and superior mechanical properties in comparison to buckypaper prepared without the addition of cellulose nanofibrils. In addition, once it is flexible and foldable, the nanocomposite film showed an increase of 375% in tensile strength and 400% in maximum stress at break. Acting as an electrode, the nanocomposite buckypaper operates with high capacitance retention at different pHs with the different dissolved redox species. The half-cell built using hydroquinone-based electrolyte should be highlighted, once it has a high specific capacitance (380.8 F g-1 to 1.0 A g-1), and a high capacitance retention capacity (216.1 F g-1 to 15 A g-1), in addition to a load transfer resistance of 0.011 Ω.